Testosterone and BMD in elite male lightweight rowers - Vinther, A.; Kanstrup, I. L.; Christiansen, E.; Ekdahl, C.; Aagaard, P. (International Journal of Sports Medicine, 2008)
The purpose of the present study was to investigate if a relationship between BMD and testosterone levels could be identified in elite male lightweight rowers. Thirteen male lightweight national team rowers had their BMD measured in a DEXA scanner. Plasma concentrations of total testosterone (TT), free testosterone (FT), dihydrotestosterone (DHT) and sex hormone binding globulin (SHBG) and additional parameters related to bone metabolism were measured. Plasma concentrations of TT, FT and DHT were in the lower part of the normal range, while BMD was close to or above normal. BMD of total body and L2 - L4 were correlated to years of training (rs: 0.59, p = 0.034 and rs: 0.73, p = 0.005) and to TT (rs: 0.56, p = 0.046 and rs: 0.63, p = 0.021). Moreover, L2 - L4 BMD was correlated to FT (rs: 0.62, p = 0.024). After adjusting for years of training, partial correlation analysis showed a significant correlation between L2 - L4 BMD and TT (rs: 0.61, p < 0.05). BMD appears to be influenced by both testosterone levels and years of training in elite male lightweight rowers. The relatively high BMD and low testosterone levels indicate that the mechanical loading induced by rowing is more important to BMD than testosterone levels. Prospective investigations are needed to elucidate potential causal relationships.